2010
DOI: 10.1007/s00264-010-0984-x
|View full text |Cite
|
Sign up to set email alerts
|

Single-centre study of hip fractures in Prague, Czech Republic, 1997–2007

Abstract: This study examines the epidemiological data of patients with hip fractures from 1997-2007. Adult patients treated for hip fracture between the years 1997-2007 were included in the study. Retrospective statistical assessment of continually gathered data focussed on epidemiology and demographics. The study involved 3,683 patients (2,678 women and 1,005 men). Patients older than 70 years accounted for 82% of all cases. There were 2.7 times more women; in patients younger than 60 years men significantly outnumber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 45 publications
2
2
0
2
Order By: Relevance
“…Mean age, the male to female ratio and fracture distribution of our series were comparable to a large cohort study of 3,683 hip fracture patients [17]. Another large series (3,240 patients) of Deakin et al found a comparable mean age and percentage of patients living in their own home prior to admission [8].…”
Section: Discussionsupporting
confidence: 83%
“…Mean age, the male to female ratio and fracture distribution of our series were comparable to a large cohort study of 3,683 hip fracture patients [17]. Another large series (3,240 patients) of Deakin et al found a comparable mean age and percentage of patients living in their own home prior to admission [8].…”
Section: Discussionsupporting
confidence: 83%
“…A total of 1,130 patients were identified, and 455 met the eligibility requirements for the study population (Table II). Three hundred and eighteen (69.9%) of the patients were female and 137 (30.1%) were male, which is comparable with male-to-female ratios reported in the literature 3 , 27 . The median age was 82.0 years (range, 60 to 99 years), and the median body mass index (BMI) was 23.8 kg/m 2 (range, 13.3 to 63.7 kg/m 2 ).…”
Section: Methodssupporting
confidence: 85%
“…Regarding the ratio between pertrochanteric and femoral neck fractures of the femur, Smektala et al 34 showed an almost equal distribution between femoral neck (n ¼ 1466) and pertrochanteric (n ¼ 1450) fractures in a retrospective study on 2916 proximal femoral fractures. Ská la-Rosenbaum 35 examined the epidemiological data of 3683 patients with hip fractures between 1997 and 2007. In this study trochanteric fractures accounted for 54.7% and femoral neck fractures for 45.3% of all proximal femoral fractures.…”
Section: Discussionmentioning
confidence: 99%